Cape Verde : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
In this study, the following statistical data are presented in detail: selected economic and financial indicators, sources and uses of resources, industrial production, consumption of petroleum products, public investment expenditure, consumer prices, monetary survey, economic classification of central government expenditure, interest rate structure, fiscal operations of central government, merchandise exports and imports, direction of trade, factor income, private and public investors, selected indicators of central government revenue, summary accounts of commercial banks, production in agriculture, livestock, and fishing, and so on.